PENERAPAN PENDEKATAN STEM UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA SD DI KABUPATEN PASURUAN - Ningsih, Tutut Hartina Ilmiah; Supriyono, Supriyono; Rahayuningsih, Sri (Universitas Bhinneka PGRI, 2024)
This study aims to improve the understanding of concepts with Science, Technology, Emgineering, and Mathematics (STEM) approaches in mathematics learning in elementary school students. The subjects of this study were Class IV teachers and 12 MI Riyadlul Ulum students for the even semester 2023/2024 academic year. Data collection techniques are observation, tests and documentation. Data analysis techniques are carried out through three stages, namely data condensation, data presentation, and concluding data. Based on the results of research on the learning process in cycle I, teacher activities obtain good qualifications (B) and student activities obtain sufficient qualifications (C). while in cycle II teacher activities have good qualifications (B) and student activities obtain good qualifications (B). Furthermore, students' understanding of concepts in the first cycle reached a percentage of 75%, in the second cycle it increased to 93%. So it can be concluded that students experience an increase in understanding concepts using a STEM approach. These findings support the integration of STEM approaches in the Merdeka curriculum in basic education to improve the quality of education.